2020
DOI: 10.21474/ijar01/10701
|View full text |Cite
|
Sign up to set email alerts
|

Pityriasis Alba: An Epidemiological and Clinical Study

Abstract: Background: Pityriasis alba is a common cutaneous disorder usually asymptomatic, hypopigmented macules with or without mild scaling are its presenting lesions. Its etiology and pathogenesis are still poorly understood. Methodology:A descriptive cross-sectional study covered all patients with Pityriasis Alba attended the dermatology department. Results:A total of 86 patients with pityriasis alba, the age range was (2-20) years with a mean age of (8.9) years. Males were 53(61.6%) patients; females were 33(38.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…All six Pityriasis alba patients were atopic and aged below 15 years. However, Hashim Mahdi Jassim et al [15] observed atopy in only 17 % of P. alba patients aged 8 months to 32 years.…”
Section: Discussionmentioning
confidence: 98%
“…All six Pityriasis alba patients were atopic and aged below 15 years. However, Hashim Mahdi Jassim et al [15] observed atopy in only 17 % of P. alba patients aged 8 months to 32 years.…”
Section: Discussionmentioning
confidence: 98%